Mends: the use of melatonin in children with neuro-developmental disorders and impaired sleep – a randomised, double-blind, placebo-controlled, parallel trial. (4th April 2011) - Appleton, R E; Gringras, P; ,
Abstract : Aims: Open-label and small crossover studies have shown that exogenous melatonin can improve sleep latency (time to fall asleep) in children with neuro-developmental disabilities including autistic spectrum disorders. Anecdotal data have also suggested that it may also improve total sleep time. The aim of this randomised study was to determine the effectiveness and safety of melatonin in improving total sleep time in this population. Methods: A double-blind, placebo-controlled study was undertaken in 21 centres in England and Wales. Children aged 3 to 15 years with neuro-developmental delay (including children with autism) and severe sleep-onset and maintenance problems, were recruited to an initial standardised behavioural intervention for 1 month. Non-responders after this period were then randomised to receive placebo or pharmaceutical grade fast release melatonin (Sourced by Alliance Pharmaceuticals and supplied by Penn Pharmaceutical Service) administered 45 min before their optimal bedtime and in escalating doses from 0.5 mg to 12 mg. Study duration was 12 weeks. The primary outcome was total sleep duration measured by nightly sleep diaries (somnologs). Secondary outcomes included sleep variables measured objectively by actigraphy and behavioural measures. Biochemical and genetic data were also collected. Results: 146 children with severe sleep problems who did not respond to behavioural intervention were randomised. Provisional results are presented and analysis was by analysis of covariance and adjusting for baseline values. The adjusted difference in mean total sleep time between the melatonin and placebo groups was 15.92 min 95% CI (−6.43 to 38.26) (p=0.16) and the unadjusted mean difference was 11.08 min (−15.91 to 38.06) (p=0.42). Conclusion: On average the children treated with melatonin slept nearly 16 min longer than those in the placebo group. However, the upper limit of the CI was less than 1 h, the minimum worthwhile difference specified at the outset of the trial. This study provides strong evidence that melatonin does not improve total sleep time by a significant amount.